Diseño de árbol solar generador de energía renovable para carga de equipos móviles - Vera Quiroz, Camilo Andres (Universidad Antonio Nariño, 2022)
This project seeks to provide a solution to the high demand for energy that occurs in the charging of mobile equipment and for which, due to the study methods and the systematization of processes in universities, there are no sources of energy. renewable energy that not only supply energy, but also contribute to the reduction of the Carbon footprint, which favors Global Warming.